Implications of the local hemodynamic forces on the formation and destabilization of neoatherosclerotic lesions. (1st December 2018) - Torii, Ryo; Stettler, Rodrigue; Räber, Lorenz; Zhang, Yao-Jun; Karanasos, Antonis; Dijkstra, Jouke; Patel, Kush; Crake, Tom; Hamshere, Steve; Garcia-Garcia, Hector M.; Tenekecioglu, Erhan; Ozkor, Muhiddin; et al.
Abstract: Objective: To examine the implications of endothelial shear stress (ESS) distribution in the formation of neoatherosclerotic lesions. Methods: Thirty six patients with neoatherosclerotic lesions on optical coherence tomography (OCT) were included in this study. The OCT data were used to reconstruct coronary anatomy. Blood flow simulation was performed in the models reconstructed from the stent borders which it was assumed that represented the lumen surface at baseline, immediate after stent implantation, and the estimated ESS was associated with the neointima burden, neoatherosclerotic burden and neointima characteristics. In segments with neointima rupture blood flow simulation was also performed in the model representing the lumen surface before rupture and the ESS was estimated at the ruptured site. Results: An inverse association was noted between baseline ESS and the incidence and the burden of neoatherosclerotic ( β = −0.60, P < 0.001, and β = −4.05, P < 0.001, respectively) and lipid-rich neoatherosclerotic tissue ( β = −0.54, P < 0.001, and β = −3.60, P < 0.001, respectively). Segments exposed to low ESS (<1 Pa) were more likely to exhibit macrophages accumulation (28.2% vs 10.9%, P < 0.001), thrombus (11.0% vs 2.6%, P < 0.001) and evidence of neointima discontinuities (8.1% vs 0.9%, P < 0.001) compared to those exposed to normal or high ESS. In segments with neointima rupture the ESS was high at the rupture site compared to the average ESS over the culprit lesion (4.00 ± 3.65 Pa vs 3.14 ± 2.90 Pa, P < 0.001). Conclusions: Local EES is associated with neoatherosclerotic lesion characteristics, which suggests involvement of ESS in the formation of vulnerable plaques in stented segments. Highlights: Shear stress regulates long term neointima proliferation in bare metal and drug eluting stents Shear stress is involved in the formation of lipid rich neoatherosclerotic lesions and regulates neointima inflammation Local hemodynamic forces and in particular high shear stress contribute to the destabilization of high-risk, vulnerable neoatherosclerotic plaques.